(untitled) (Town and Regional Planning, 1990)
In an earlier research study of South African towns (excluding the metropolitan areas and large cities) an analysis of a comprehensive range of services, from those offered by general trading stores to supermarkets and institutional services, was undertaken. On the basis of this analysis it was shown that by dividing the total population in the study area by the number of each of these services a mean service count for each service could be obtained. For practical purposes the figures thus obtained were taken to reflect the threshold values of the particular services. By adding the values of the services in each town it was possible to award a service count to each town and to establish a hierarchical ranking from strategic core towns to, successively, regional centres, district towns, ward towns and unclassified ad hoc settlements. In this study nine standard local services were used to determine a service count for a number of district towns. By subtracting the resident population of a town from its service count the number of people dependent on that town from the surrounding rural area was computed. The area of this rural dependancy was calculated from the average density of the district and hence the radius or average reach of the to